(untitled) (Colloquia Comparativa Litterarum, 2025)
It has become a tradition to use the succession of Gogol’s short novel The Nose from Laurence Sterne’s Life and Opinions of Tristram Shandy as a key to its interpretation, and to identify its kinship to the ‘noseology’ in 1820s’ and 1830s’ Russian literature and the peculiar type of Russian Sternianism, which originated as a result of the novel’s reception in Russia. In this research perspective, set originally by V. V. Vinogradov, so much work has been completed that its potential seems to have been exhausted. Nevertheless, certain vagueness and several logical gaps have been identified in the established visions about Sterne’s influence on Gogol. The task of the present study is to bridge these inadequacies and to clarify the mechanisms that helped transform Sterne’s ‘noseology’ into the puzzling world of Gogol’s The Nose. The examination conducted in this paper demonstrates that the essential link between the whimsical logic of Gogol’s short novel, and especially the paradoxical substantiation of the theme of the nose in it, on the one hand, and Sterne’s novel Tristram Shandy, on the other, is manifested as re-actualization of an entire network of motifs that were established by the source novel and were reproduced in specific ways both in The Nose and in Gogol’s other works. As a result of this process, strange associative groupings that seem to have been deprived of meaning were set firmly as fixed configurations. A characteristic of the specific mechanism manifested in Gogol’s autotextuality is the fact that the cluster of interconnected images and notions issuing from Sterne’s novel was repeated again by means of varying combinations of elements. Each of these single derivative substantiations is incomplete with regard to the paradigm, and though inexhaustible and scattered throughout various texts by Gogol, they still remain recognizable parts of a common constellation, whose prototype was created by Sterne.